Antioxidant activity of basil and oregano extracts added to soybean oil for accelerated storage test - Pitaro, S. [UNESP]; Fiorani, L. [UNESP]; Jorge, N. [UNESP] (Wiley, 2013)
The objective of this research was to evaluate the antioxidant activity of extract of basil and oregano, and its synergistic effect when added to soybean oil and subjected to accelerated storage test. Extracts of basil, oregano and mixtures of both were applied to soybean oil at a concentration of 2.000mg/kg, then the extracts were heated in an oven at 60C for a period of 10 days. Samples were taken every 2 days and analyzed for concentrations of peroxides and conjugated dienes. Synthetic antioxidant tert-butylhydroquinone (TBHQ) at a concentration of 50mg/kg and soybean oil free antioxidant (control) subject to the same conditions were used as benchmarks. The results showed that the antioxidant effect decreases according to oil heating for all treatments. However, the synthetic antioxidant showed superior protection to the soybean oil during the formation of primary oxidation compounds, followed by the natural extracts, which showed no synergism. © 2012 Wiley Periodicals, Inc.
Keywords: Accelerated storages; Anti-oxidant activities; Antioxidant effect; Conjugated dienes; Oregano extracts; Synergistic effect; Synthetic antioxidants; Tert-butylhydroquinone (tBHQ); Antioxidants; Soybean oil; Glycine max; Ocimum; Origanum